Semi-guided waves in integrated optical waveguide structures - Ebers, Lena
In dieser Arbeit wird die elektromagnetische Wellenausbreitung in integrierten optischen Wellenleitern mit Hilfe von halb analytischen und numerischen Simulationsmethoden untersucht. Im ersten Teil werden 2-D Si/SiO2-Wellenleiterkonfigurationen mit hohem Brechungsindexkontrast betrachtet. Die Strukturen werden mit halb geführten Wellen unter schrägen Ausbreitungswinkeln angeregt. Dadurch kann die Leistungsübertragung zu bestimmten ausgehenden Moden unterdrückt werden, wodurch vollständig verlustfreie Systeme entstehen. Zusätzlich dient die Anregung mit einem seitlich begrenzten, einfallenden Wellenbündel aus halb geführten Wellen dazu, praktisch relevantere 3-D Konfigurationen zu realisieren. Darüber hinaus wird eine schrittweise Winkelspektrum-Methode vorgestellt, die es ermöglicht, in Kombination mit voll vektoriellen 2-D Finite-Elemente-Lösungen für Teilprobleme mit geringerer Komplexität, die Wellenausbreitung in planaren, linsenförmigen Wellenleitern numerisch in drei Raumrichtungen zu berechnen. Im zweiten Teil dieser Arbeit wird die Ausbreitung in Wellenleiterstrukturen aus Lithiumniobat untersucht, welche für quantenoptische Effekte genutzt werden. Zur Detektion einzelner Photonen werden supraleitende Nanodrähte auf eindiffundierten Lithiumniobat Wellenleitern mit zusätzlicher Taperschicht aus Silizium betrachtet. Um die Wellenausbreitung in diesen 3-D Wellenleitern zu beschreiben, wird eine einseitig gerichtete Finite-Elemente „Modal Matching“ Methode eingeführt. Abschließend werden Rippenwellenleiter aus Lithiumniobat analysiert, die auf Siliziumdioxid Plattformen aufgebracht sind. Der Schwerpunkt liegt hier auf dem nichtlinearen „Parametric Down-Conversion“ Prozess, der für die Erzeugung verschränkter Photonen verwendet wird.
Keywords: tet_topic_waveguide

Finding Optimal Arms in Non-stochastic Combinatorial Bandits with Semi-bandit Feedback and Finite Budget - Brandt, Jasmin; Haddenhorst, Björn; Bengs, Viktor; Hüllermeier, Eyke (arXiv:2202.04487)
We consider the combinatorial bandits problem with semi-bandit feedback under finite sampling budget constraints, in which the learner can carry out its action only for a limited number of times specified by an overall budget. The action is to choose a set of arms, whereupon feedback for each arm in the chosen set is received. Unlike existing works, we study this problem in a non-stochastic setting with subset-dependent feedback, i.e., the semi-bandit feedback received could be generated by an oblivious adversary and also might depend on the chosen set of arms. In addition, we consider a general feedback scenario covering both the numerical-based as well as preference-based case and introduce a sound theoretical framework for this setting guaranteeing sensible notions of optimal arms, which a learner seeks to find. We suggest a generic algorithm suitable to cover the full spectrum of conceivable arm elimination strategies from aggressive to conservative. Theoretical questions about the sufficient and necessary budget of the algorithm to find the best arm are answered and complemented by deriving lower bounds for any learning algorithm for this problem scenario.

Work-in-Progress: The Potential of Interactive Scripts – Supporting Conceptual Understanding and Collaborative Problem-Solving Skills - Temmen, Katrin; Kersten, Peter; Schäfer, Dominik (Mobility for Smart Cities and Regional Development - Challenges for Higher Education)

Reibscheibe für eine Reibungskupplung - Zimmer, Detmar; Blumenthal, Lars Martin; Schadomsky, Magnus
Es ist eine Reibscheibe (18) für eine Reibungskupplung (10) vorgesehen mit einem zwischen Druckplatten (14, 16, 38) verklemmbaren Rotorring (32), Reibbelägen zur Herstellung eines Reibschlusses des Rotorrings (32) mit der jeweiligen Druckplatte, (14, 16, 38), einem axial feststehenden Wellenelement (20) zur Übertragung eines Drehmoments und mindestens einem mit dem Rotorring (32) und mit dem Wellenelement (20) im Wesentlichen drehfest verbundenen und in axialer Richtung elastisch nachgiebigen Federelement (34) zur elastischen axialen Verlagerung des Rotorrings (32) relativ zum Wellenelement (20), wobei der Rotorring (32) zwischen einer Offenstellung, in welcher das Federelement (34) entspannt ist, und einer Schließstellung, in welcher das Federelement (34) von mindestens einer Druckplatte (14, 16, 38) verspannt ist, im Wesentlichen in axialer Richtung parallelverschiebbar ist. Durch den über den vergleichsweise geringen erforderlichen axialen Verlagerungsweg federnd an dem axial unbeweglichen Wellenelement (20) angebundenen die Reibbeläge tragenden Rotorring (32) kann bei geringen Herstellungskosten unnötige Reibung vermieden werden, so dass eine verschleißarme und geräuscharme lösbare Koppelung von Bauteilen ermöglicht ist.

DASC-PM v1.1 - Ein Vorgehensmodell für Data-Science-Projekte - Schulz, Michael; Neuhaus, Uwe; Kaufmann, Jens; Kühnel, Stephan; Alekozai, Emal M.; Rohde, Heiko; Hoseini, Sayed; Theuerkauf, René; Badura, Daniel; Kerzel, Ulrich; Lanquillon, Carsten; Daurer, Stephan; et al.

Size‐Dependent Strain Relaxation in InAs Quantum Dots on Top of GaAs(111)A Nanopillars - Riedl, Thomas; Kunnathully, Vinay S.; Trapp, Alexander; Langer, Timo; Reuter, Dirk; Lindner, Jörg K. N. (Advanced Materials Interfaces)
Keywords: Mechanical Engineering; Mechanics of Materials

Comparative Evaluation of MVAC-LVDC SST and Hybrid Transformer Concepts for Future Datacenters - Huber, Jonas; Wallmeier, Peter; Pieper, Ralf; Schafmeister, Frank; Kolar, Johann (Proc. 9th IEEJ International Power Electronics Conference (IPEC))

Turnpike Property in Optimal Microbial Metabolite Production - Caillau, Jean-Baptiste; Djema, Walid; Gouzé, Jean-Luc; Maslovskaya, Sofya; Pomet, Jean-Baptiste (Journal of Optimization Theory and Applications)
Abstract We consider the problem of maximization of metabolite production in bacterial cells formulated as a dynamical optimal control problem (DOCP). According to Pontryagin’s maximum principle, optimal solutions are concatenations of singular and bang arcs and exhibit the chattering or Fuller phenomenon, which is problematic for applications. To avoid chattering, we introduce a reduced model which is still biologically relevant and retains the important structural features of the original problem. Using a combination of analytical and numerical methods, we show that the singular arc is dominant in the studied DOCPs and exhibits the turnpike property. This property is further used in order to design simple and realistic suboptimal control strategies.
Keywords: Applied Mathematics; Management Science and Operations Research; Control and Optimization

A Survey of Methods for Automated Algorithm Configuration - Schede, Elias; Brandt, Jasmin; Tornede, Alexander; Wever, Marcel Dominik; Bengs, Viktor; Hüllermeier, Eyke; Tierney, Kevin (arXiv:2202.01651)
Algorithm configuration (AC) is concerned with the automated search of the most suitable parameter configuration of a parametrized algorithm. There is currently a wide variety of AC problem variants and methods proposed in the literature. Existing reviews do not take into account all derivatives of the AC problem, nor do they offer a complete classification scheme. To this end, we introduce taxonomies to describe the AC problem and features of configuration methods, respectively. We review existing AC literature within the lens of our taxonomies, outline relevant design choices of configuration approaches, contrast methods and problem variants against each other, and describe the state of AC in industry. Finally, our review provides researchers and practitioners with a look at future research directions in the field of AC.

Giant Photoelasticity of Polaritons for Detection of Coherent Phonons in a Superlattice with Quantum Sensitivity - Kobecki, Michal; Scherbakov, Alexey V.; Kukhtaruk, Serhii M.; Yaremkevich, Dmytro D.; Henksmeier, Tobias; Trapp, Alexander; Reuter, Dirk; Gusev, Vitalyi E.; Akimov, Andrey V.; Bayer, Manfred (Physical Review Letters)
Keywords: General Physics and Astronomy

Testing and modeling blast loading of a sandwich structure cored with a bio-inspired (balanus) core - Tuzgel, Firat; Akbulut Irmak, Emine Fulya; Guzel, Erkan; Yucesoy, Atacan; Sahin, Selim; Tasdemirci, Alper; Guden, Mustafa (Thin-Walled Structures)
Keywords: Mechanical Engineering; Building and Construction; Civil and Structural Engineering

Betrieb von Federkraftbremsen bei hohen Gleitgeschwindigkeiten - Schadomsky, Magnus; Zimmer, Detmar (Konstruktion)
Federkraftbremsen sind weit verbreitete Komponenten der Antriebstechnik, ansteigend mit abnehmender Größe erreichen sie aktuell Drehzahlen von bis zu 5 000 min−1. Es besteht ein Trend zu schnell laufenden Antrieben, mit Drehzahlen von 10 000 min−1 und darüber. Bisher sind wenig Kenntnisse über das Verhalten des Reibwerts und -moments herkömmlicher Federkraftbremsen mit kostengünstigen organischen Reibbelägen bei diesen Einsatzbedingungen bekannt. Daher wurde ein Prüfstand entwickelt, der die Untersuchung bei Gleitgeschwindigkeiten von bis zu 50 m/s bei verschiedenen Lastträgheiten ermöglicht. Die Versuche zeigten, dass bei begrenzten Reibarbeiten die herkömmliche Federkraftbremse durchaus das Nennbremsmoment bei höheren Gleitgeschwindigkeiten erreicht.
Keywords: Federkraftbremse; Gleitgeschwindigkeit

Ammonium enables reversible aqueous Zn battery chemistries by tailoring the interphase - Ma, Lin; Pollard, Travis P.; Zhang, Yong; Schroeder, Marshall A.; Ren, Xiaoming; Han, Kee Sung; Ding, Michael S.; Cresce, Arthur V.; Atwater, Terrill B.; Mars, Julian; Cao, Longsheng; Steinrück, Hans-Georg; et al. (One Earth)
Keywords: Earth and Planetary Sciences (miscellaneous); General Environmental Science

Supporting Young Immigrants in Their Transition From School to Work? A Staff Perspective on Challenges of Vocational Integration Classes - Goller, Michael (International Journal for Research in Vocational Education and Training)
Context: The implementation of successful measures to support immigrants' integration in cultural, social, and economic life can be considered as one of today's greatest challenges for many societies. This is especially true for adolescent immigrants who have not yet been able to finish education or gain qualifications relevant to joining the labour market. That is why many receiving countries have developed and implemented special programmes that aim at supporting immigrants' integration by facilitating their employability. Unfortunately, not much is known about the process of implementing these programmes or about how education systems, schools, and teachers are dealing with the new situation and target group. In this contribution, the implementation, development, and challenges of German Vocational Integration Classes (VIC), as an example of comparable programmes in the EU, are investigated to address this research gap. The paper considers the following exploratory research questions: (a) What challenges have been experienced by teachers and social workers in the implementation of VIC as well as in the integration of immigrants into the labour market in recent years? (b) How can these challenges be met in the long run and how should VIC be developed to better achieve its aims? Methods: To answer these questions, a sequential qualitative study containing questionnaire and interview elements was conducted. First, teachers and social workers involved in VIC filled in a questionnaire about their experiences and experienced challenges in implementing VIC (N = 46). Then, supplementing interviews were conducted with participants from the first sample in order to generate further insights and to contextualise the findings from the first study part (N = 14). Findings: From the respondents' answers, it appears that the VIC programme is well implemented. The results show, however, that central challenges continue to exist. This concerns, for example, legal regulations or the development of adequate curricula, but also the scope and quality of language education. In addition, problems have also been identified with regard to students' culture-specific education and their individual attitudes. These prevailing problems seem to affect schooling and educational processes. In addition, respondents report feeling left alone to deal with problems and that their experiences from their daily work in VIC and with immigrants are not sufficiently taken into account in policy and school-related decisions. Conclusions: Although VIC seems well implemented, key challenges remain in the view of the participants. It was found that teachers cannot solve many of the identified problems themselves, as they require action at the level of policy or school organisation. For staff, this can be accompanied by increased stress and demotivation. For the young immigrants, the existing challenges can have a long-term impact on school success and transition to vocational education and training. The study thus highlights the importance of targeted and holistic strategies to support immigrant integration through education.
Keywords: Immigration; Educational Policy; Employability; Mixed Methods; VET; Vocational Education and Training; Transitions From Education and Training to Employment

Coalition formation versus free riding in rent-seeking contests - Block, Lukas (Quick And Easy Journal Title)
We study lobby group formation in a two-stage model where the players rst form lobby groups that then engage in a rent-seeking contest to inuence the legislator. However, the outcome of the contest aects all players according to the ideological distance between the implemented policy and the players' preferences. The players can either lobby by themselves, form a coalition of lobbyists or free ride. We nd that free coalition formation is reasonable if either players with moderate preferences face lobby groups with extreme preferences, or if there are two opposing coalitions with an equal number of members. Otherwise, there are always free riders among the players.
Keywords: Group formation; Rent-seeking; Free riding

Quantification of the adhesive coupling of layered structures using guided ultrasonic waves - Nicolai, Marcel; Zeipert, Henning; Lugovtsova, Yevgeniya; Bulling, Jannis; Johannesmann, Sarah; Prager, Jens; Henning, Bernd (Fortschritte der Akustik - DAGA 2022)

Conformal Pressure and Fast-Charging Li-Ion Batteries - Cao, Chuntian; Steinrück, Hans-Georg; Paul, Partha P; Dunlop, Alison R.; Trask, Stephen E.; Jansen, Andrew; Kasse, Robert M; Thampy, Vivek; Yusuf, Maha; Nelson Weker, Johanna; Shyam, Badri; Subbaraman, Ram; et al. (Journal of The Electrochemical Society)
Abstract Batteries capable of extreme fast-charging (XFC) are a necessity for the deployment of electric vehicles. Material properties of electrodes and electrolytes along with cell parameters such as stack pressure and temperature have coupled, synergistic, and sometimes deleterious effects on fast-charging performance. We develop a new experimental testbed that allows precise and conformal application of electrode stack pressure. We focus on cell capacity degradation using single-layer pouch cells with graphite anodes, LiNi0.5Mn0.3Co0.2O2 (NMC532) cathodes, and carbonate-based electrolyte. In the tested range (10 – 125 psi), cells cycled at higher pressure show higher capacity and less capacity fading. Additionally, Li plating decreases with increasing pressure as observed with scanning electron microscopy (SEM) and optical imaging. While the loss of Li inventory from Li plating is the largest contributor to capacity fade, electrochemical and SEM examination of the NMC cathodes after XFC experiments show increased secondary particle damage at lower pressure. We infer that the better performance at higher pressure is due to more homogenous reactions of active materials across the electrode and less polarization through the electrode thickness. Our study emphasizes the importance of electrode stack pressure in XFC batteries and highlights its subtle role in cell conditions.
Keywords: Materials Chemistry; Electrochemistry; Surfaces; Coatings and Films; Condensed Matter Physics; Renewable Energy; Sustainability and the Environment; Electronic; Optical and Magnetic Materials

Corrosion fatigue behavior of electron beam melted iron in simulated body fluid - Wackenrohr, Steffen; Torrent, Christof Johannes Jaime; Herbst, Sebastian; Nürnberger, Florian; Krooss, Philipp; Ebbert, Christoph; Voigt, Markus; Grundmeier, Guido; Niendorf, Thomas; Maier, Hans Jürgen (npj Materials Degradation)
Abstract Pure iron is very attractive as a biodegradable implant material due to its high biocompatibility. In combination with additive manufacturing, which facilitates great flexibility of the implant design, it is possible to selectively adjust the microstructure of the material in the process, thereby control the corrosion and fatigue behavior. In the present study, conventional hot-rolled (HR) pure iron is compared to pure iron manufactured by electron beam melting (EBM). The microstructure, the corrosion behavior and the fatigue properties were studied comprehensively. The investigated sample conditions showed significant differences in the microstructures that led to changes in corrosion and fatigue properties. The EBM iron showed significantly lower fatigue strength compared to the HR iron. These different fatigue responses were observed under purely mechanical loading as well as with superimposed corrosion influence and are summarized in a model that describes the underlying failure mechanisms.
Keywords: Materials Chemistry; Materials Science (miscellaneous); Chemistry (miscellaneous); Ceramics and Composites

Oxide Modified Iron in Electron Beam Powder Bed Fusion—From Processability to Corrosion Properties - Torrent, Christof J. J.; Krooß, Philipp; Huang, Jingyuan; Voigt, Markus; Ebbert, Christoph; Knust, Steffen; Grundmeier, Guido; Niendorf, Thomas (Alloys)
Additive manufacturing (AM) processes are not solely used where maximum design freedom meets low lot sizes. Direct microstructure design and topology optimization can be realized concomitantly during processing by adjusting the geometry, the material composition, and the solidification behavior of the material considered. However, when complex specific requirements have to be met, a targeted part design is highly challenging. In the field of biodegradable implant surgery, a cytocompatible material of an application-adapted shape has to be characterized by a specific degradation behavior and reliably predictable mechanical properties. For instance, small amounts of oxides can have a significant effect on microstructural development, thus likewise affecting the strength and corrosion behavior of the processed material. In the present study, biocompatible pure Fe was processed using electron powder bed fusion (E-PBF). Two different modifications of the Fe were processed by incorporating Fe oxide and Ce oxide in different proportions in order to assess their impact on the microstructural evolution, the mechanical response and the corrosion behavior. The quasistatic mechanical and chemical properties were analyzed and correlated with the final microstructural appearance.

Measurement of material degradation in dependence of shear rate, temperature, and residence time - Schall, Christoph Wilhelm Theodor; Schöppner, Volker (Polymer Engineering and Science)
Keywords: Computing Resources Provided by the Paderborn Center for Parallel Computing